Three-dimensional hierarchical Co3O4/CuO nanowire heterostructure arrays on nickel foam for high-performance lithium ion batteries - Wang, Jiexi; Zhang, Qiaobao; Li, Xinhai; Xu, Daguo; Wang, Zhixing; Guo, Huajun; Zhang, Kaili (Nano energy, 2014)
Novel three-dimensional (3D) hierarchical Co3O4/CuO nanowire (NW) arrays on nickel foam composed of CuO NW stems and Co3O4 nanosheet branches are synthesized by combining a facile, scalable, and cost-effective thermal oxidation method with a simple but powerful chemical bath deposition followed by a calcination process. These arrays are further investigated as binder- and conductive-agent-free anodes for lithium-ion batteries (LIBs). The smart hybridization of CuO NWs and Co3O4 nanosheets into hierarchical core/shell array configuration results in remarkably enhanced electrochemical performances with good cycle performance, high reversible capacity, and excellent rate capability compared with pure CuO NW and single net-like Co3O4 nanosheets. A high reversible capacity of 1191mAhg−1 with 90.9% capacity retention after 200 cycles at a current density of 200mAg−1, and reversible capacity up to 810mAhg−1 even after 500 cycles at a current density as high as 1000mAg−1 can be maintained. The superior electrochemical performances of electrodes composed of hierarchical Co3O4/CuO NW arrays connected directly on nickel foam make them potential anode materials for high-performance LIBs. [Display omitted] •Electron beam evaporation followed by oxidation to prepare CuO NWs on Ni foam.•Novel chemical bath deposition of Co3O4 to form 3D CuO/Co3O4 core/shell NW arrays.•Excellent cyclability, high capacity, and good rate capability as used in LIBs.•Synergetic effect of CuO NW core/Co3O4 shell results in remarkable performance.